Screening for Active Compounds of Acorus calamus against SARS-CoV-2 Viral Protease and Mechanism Prediction - Yuting Huang; Zhaoxing Li; Yuan Ma; Qianqian Wu; Jianping Kong; Lijuan Zhao; Shunxiang Li; Juan Li (MDPI AG, 2024)
COVID-19, caused by SARS-CoV-2, has emerged as the most destructive emerging infectious disease of the 21st century. Vaccination is an effective method to combat viral diseases. However, due to the constant mutation of the virus, new variants may weaken the efficacy of vaccines. In the current field of new coronavirus research, viral protease inhibitors have emerged as a highly regarded therapeutic strategy. Nevertheless, existing viral protease inhibitors do not fully meet the therapeutic needs. Therefore, this paper turned to traditional Chinese medicine to explore new active compounds. This study focused on 24 isolated compounds from Acorus calamus L. and identified 8 active components that exhibited significant inhibitory effects on SARS-CoV-2 PLpro. Among these, the compound 1R,5R,7S-guaiane-4R,10R-diol-6-one demonstrated the best inhibitory activity with IC50 values of 0.386 ± 0.118 μM. Additionally, menecubebane B and neo-acorane A exhibited inhibitory activity against both Mpro and PLpro proteases, indicating their potential as dual-target inhibitors. The molecular docking results confirmed the stable conformations of these compounds with the key targets and their good activity. ADMET and Lipinski's rule analyses revealed that all the small molecule ligands possessed excellent oral absorption properties. This study provides an experimental foundation for the discovery of promising antiviral lead compounds.